1977
DOI: 10.1007/bf00913091
|View full text |Cite
|
Sign up to set email alerts
|

“Think Aloud”: A program for developing self-control in young aggressive boys

Abstract: "Think Aloud" was designed as a training program to improve self-control in 6- to 8-year-old boys. It involved modeling and verbalization of cognitive activity to foster use of verbal mediation skills in dealing with both cognitive and interpersonal problems. It was hypothesized that this training would lead to improvement in test performance and teacher ratings of classroom behavior in hyperaggressive boys. Twelve aggressive second grade boys participated in daily, 30-minute, individual sessions for 6 weeks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0
2

Year Published

1982
1982
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(48 citation statements)
references
References 5 publications
1
44
0
2
Order By: Relevance
“…Training included repetition of coping statements in role play situations, first aloud, then in whispers, and finally, silently (Meichenbaum, 1977). The final component involved instruction in problem solving skills (Camp, Blom, Herbert, & van Doorninck, 1977). This involved a four-step problem-solving process, as follows: (1) What is the problem?…”
Section: Interventionmentioning
confidence: 99%
“…Training included repetition of coping statements in role play situations, first aloud, then in whispers, and finally, silently (Meichenbaum, 1977). The final component involved instruction in problem solving skills (Camp, Blom, Herbert, & van Doorninck, 1977). This involved a four-step problem-solving process, as follows: (1) What is the problem?…”
Section: Interventionmentioning
confidence: 99%
“…The results, though mixed, suggest that self-instruction training was effective in increasing prosocial behavior (Camp, et al, 1977) and in decreasing distractibility, aggressiveness, and restlessness (Kendall, 1982;Kendall & Zupan, 1981).…”
mentioning
confidence: 90%
“…Brown et al (1981) reported on techniques for enhancing learning to learn among EMR and remedial students. The "turtle technique" (Robin, Schneider, & Dolnick, 1977;Schneider, 1974) and a "think aloud" program (Camp, Blom, Hebert, & Van Doorninck, 1977) have been developed to teach delayed responding and social problem solving to aggressive children. Self-instructional training has been applied to a host of behavioral and academic problems among both normal and exceptional students (Meichenbaum, 1977;Meichenbaum & Asarnow, 1979).…”
Section: Instructional Theory and Researchmentioning
confidence: 99%